SENOMAN-KELOVEY UNDERGROUND WATER COMPLEX HYDROGEOCHEMISTRY CONDITIONS CHANGES IN KYIV BASED ON LONG-TERM OBSERVATIONS - KOSHLIAKOVA, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The methodology and results of senoman-kelovey underground water complex hydrogeochemistry conditions investigations in Kyiv based on long-term observations are state. At analysis statistical technology are utilized, including test of hypothesis about normal (logarithmically normal) distribution law and determining sampling belong to the same universal set. In outcome it is possible to display the dynamics of the underground water complex hydrogeochemistry conditions. The results can serve as a basis for future investigations to explain changes of the separate components concentrations in underground water.